Implementation of e-Learning Based on Learning Management System Using Discovery Learning Method for Disabilities Students - Amrulloh, Roni; Rahadi, Irwan; Yuliatin, Riyana Rizki; Hadi, Yul Alfian; Ramdhani, Sandy (Universitas Hamzanwadi, 2021)
Inclusive learning for students with disabilities is a must that must be done in learning. The purpose of this study is to look at the application of Discovery Learning learning to students with physical disabilities and mild disabilities in the learning process especially in learning advanced speaking skills. The method used is to use the type of development Borg & Gall by using 7 stages which are divided into 3 parts, namely preliminary studies, product development and trials and finalization. The results of this study are Introduction (Rationalization of innovation, Discovery Learning models, Supporting theories of learning model development); Learning model with agreement on Discovery Learning (Discovery Learning learning component and learning model component); and Instructions on the implementation of the learning problem learning model (Planning, Implementation, and Evaluation) equipped with videos of the implementation of learning activities. In addition, the learning process produces learning videos as a result of learning the activity.Keywords: Mentally Disability, Physical Disability, Discovery Learning, Students, Literary Criticism